Autoinducer-2 enhances the defense of Vibrio furnissii against oxidative stress and DNA damage by modulation of c-di-GMP signaling via a two-component system - Heng Zhang; Wenjin Zhao; Wenguang Yang; Huimin Zhang; Xinyu Qian; Kai Sun; Qiao Yang; Xihui Shen; Lei Zhang (mBio)
ABSTRACT As a universal language across the bacterial kingdom, the quorum sensing signal autoinducer-2 (AI-2) can coordinate many bacterial group behaviors. However, unknown AI-2 receptors in bacteria may be more than what has been discovered so far, and there are still many unknown functions for this signal waiting to be explored. Here, we have identified a membrane-bound histidine kinase of the pathogenic bacterium Vibrio furnissii, AsrK, as a receptor that specifically detects AI-2 under low boron conditions. In contrast with another well-known AI-2 receptor LuxP that recognizes the borated form of AI-2, AsrK is found to show higher affinity with AI-2 under borate-depleted conditions, and thus boron has a negative effect on AI-2 sensing by AsrK in regulation of the biofilm and motility phenotypes. AI-2 binds to the extracytoplasmic dCache_1 domain of AsrK to inhibit its autokinase activity, thus decreasing the phosphorylation level of its cognate response regulator AsrR and activating the phosphodiesterase activity of AsrR to degrade the cellular second messenger cyclic di-GMP (c-di-GMP). AI-2 perception by the AsrK-AsrR system remarkably reduces intracellular c-di-GMP levels and enhances tolerance of V. furnissii to oxidative stress and DNA damage by upregulating the transcription of universal stress proteins including UspA1, UspA2, and UspE. Our study reveals a previously unrecognized mechanism for AI-2 detection in bacteria and also provides new insights into the important role of AI-2 in bacterial defense against oxidative stress and DNA damage.IMPORTANCEThe QS signal AI-2 is widely synthesized in bacteria and has been implicated in the regulation of numerous bacterial group behaviors. However, in contrast to the wide distribution of this signal, its receptors have only been found in a small number of bacterial species, and the underlying mechanisms for the detection of and response to AI-2 remain elusive in most bacteria. It is worth noting that the periplasmic protein LuxP is the uniquely identified receptor for AI-2 in Vibrio spp. Here, we identify a second type of AI-2 receptor, a membrane-bound histidine kinase with a periplasmic dCache_1 sensory domain, in a member of the genus Vibrio, and thus show that AI-2 enhances the defense of V. furnissii against oxidative stress and DNA damage by modulation of c-di-GMP signaling via the AsrK-AsrR two-component system. Our results reveal a previously unrecognized AI-2 sensing mechanism and expand our understanding of the physiological roles of AI-2 in bacteria.